Analysis of Mortality Data UCoD with MMDS Tables at Hospital X in 2022 : Analisis Data Kematian UCoD dengan Tabel MMDS di Rumah Sakit X tahun 2022 - Anisa Zahra, Putri Anisa; Kurniasih, Dewi Lena Suryani; Kamelia, Emma; Junaedi, Fadil Ahmad (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
The utilization of the primary cause of death is crucial for the control of fatal illnesses. Hospital X cause of death certificate is utilized, although not in accordance with the idea in ICD-10 volume 2. The correctness of the coding was verified by attempts to derive the UCoD using the MMDS table. This study seeks to evaluate UCoD mortality statistics using the MMDS table and ICD-10. This kind of quantitative study uses a descriptive design. Based on the diagnosis entered in the medical record, coding is used in hospital X as the primary cause of death. According to mortality data, some illnesses that lack a UCoD are the primary causes of patient deaths. In this investigation, 79 samples of death data were used, 57 of which had the right death code and 22 of which did not. The study's findings revealed that there were 79 death records for UCoD without supporting documentation for 44 death records and 35 death records with an incorrect sequence. It is important to create SOP related to mortality coding, conduct outreach on mortality coding, and implement death certificates in order to implement the fundamental cause of death, which has not yet been done, and to acquire correct death data reports.